Genome rearrangements derived from homoeologous recombination following allopolyploidy speciation in coffee. (23rd April 2014) - Lashermes, Philippe; Combes, Marie‐Christine; Hueber, Yann; Severac, Dany; Dereeper, Alexis
Summary Allopolyploidization is widespread and has played a major role in flowering plant diversification. Genomic changes are common consequences of allopolyploidization, but their mechanisms of occurrence and dynamics over time are still poorly understood. Coffea arabica, a recently formed allotetraploid, was chosen as a model to investigate genetic changes in allopolyploid using an approach that exploits next‐generation sequencing technologies. Genes affected by putative homoeolog loss were inferred by comparing the numbers of single‐nucleotide polymorphisms detected using RNA‐seq in individual accessions of C. arabica, and between accessions of its two diploid progenitor species for common sequence positions. Their physical locations were investigated and clusters of genes exhibiting homoeolog loss were identified. To validate these results, genome sequencing data were generated from one accession of C. arabica and further analyzed. Genomic rearrangements involving homoeologous exchanges appear to occur in C. arabica and to be a major source of genetic diversity. At least 5% of the C. arabica genes were inferred to have undergone homoeolog loss. The detection of a large number of homoeologous exchange events (HEEs) shared by all accessions of C. arabica strongly reinforces the assumption of a single allopolyploidization event. Furthermore, HEEs were specific to one or a few accessions, suggesting that HEE accumulates gradually. Our results provide evidence for the important role of HEE in allopolyploid genome evolution.